Supporting object oriented languages on the Comandos platform - CAHILL, VINNY (Commission of the European, 1991)
The Comandos project 3 is designing and implementing a platform to support distributed persistent applications. In particular the platform supports the object oriented style of programming. An essential requirement of the Comandos platform is that it must support applications written in a variety of existing as well as new (object oriented) programming languages. Moreover, the platform must support interworking between different languages. Each language may naturally have its own object model and execution structures implemented by a language specific runtime system. Rather than forcing each language to adopt a common object model and execution structures in order to exploit the distribution and persistence support provided by the Comandos platform, Comandos provides a generic runtime system on top of which individual language's specific runtimes may be implemented. In this paper we show how a language specific runtime for an existing language such as C++ can be constructed above the...
Conference Proceedings of ESPRIT
ESPRIT
PUBLISHED
Brussels, Belgium
Keywords: Computer Science